PENGARUH PEMANFAATAN MEDIA SOSIAL INSTAGRAM TERHADAP KINERJA BISNIS UMKM KULINER DI KOTA MAKASSAR - Arum Adityaningrum Darmiati; Muhammad Hidayat; Fitriani Latif (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze and prove the influence of Instagram social media utilization as measured through Instagram Content, Intensity of Use, and Flexibility of Utilization on the Business Performance of Culinary MSMEs in Makassar City. Method: This study uses a quantitative approach by distributing questionnaires to 100 respondents who are Culinary MSMEs in Makassar City. Data were analyzed using Multiple Regression Analysis techniques with F Test (simultaneous) and t Test (partial). Results: The results of the study show that simultaneously (F Test), the variables Instagram Content, Intensity of Use, and Flexibility of Utilization together have a positive and significant influence on MSME Business Performance. Partially (t Test), it was found that Instagram Content and Flexibility of Utilization were proven to have a positive and significant influence on MSME Business Performance. However, the variable Intensity of Use was partially proven to have no significant effect. Further results show that Flexibility of Utilization is the variable that has the most dominant influence in improving the Business Performance of Culinary MSMEs. Conclusions and Implications: The flexibility of MSMEs in utilizing various innovative features on Instagram (such as Stories, Reels, and Instagram Shopping) is more crucial in boosting business performance than simply posting frequency or intensity. Culinary MSMEs are advised to focus on strategies for adapting to new features and improving content quality to achieve optimal returns from their digital marketing activities.